Observer-rated outcomes of communication-centered treatment for adults who stutter: A social validation study. - Courtney T Byrd; Geoffrey A Coalson; Danielle Werle (PLoS ONE)
Previous studies have reported that adults who stutter demonstrate significant gains in communication competence, per self-ratings and clinician-ratings, upon completion of a communication-centered treatment, or CCT. The purpose of this social validation study was to determine whether communication competence ratings reported by untrained observers are consistent with client and clinician judgments of communication competence gains following CCT. Eighty-one untrained observers completed an online survey that required each to view one of two videos depicting an adult who stutters during a mock interview recorded prior to CCT or after CCT. Observers were then asked to rate the communication competence of the interviewee on a 100-point visual analog scale and provide additional demographic information. Communication competence of the adult who stutters who had completed CCT was rated significantly higher in their post-treatment video. Upon controlling for two demographic factors found to be associated with observer ratings (years of education, years the observers had known an adult who stutters), significantly higher ratings of communication competence for the post-treatment video were maintained. These preliminary findings provide social validity for CCT by demonstrating that the gains in communication competence reported in previous studies through clinician and client observations are also reported by untrained observers who are not familiar with CCT.